Optical Absorption of the Antitrypanocidal Drug Benznidazole inWater - Eveline M. Bezerra; João R. Bezerra-Neto; Francisco A. M. Sales; Ricardo P. dos Santos; Alice M. C. Martins; Pedro de Lima-Neto; Ewerton W. S. Caetano; Eudenilson L. Albuquerque; Valder N. Freire (Molecules, 2014)
UV-vis optical absorption spectra of the antitrypanocidal drug benznidazole solvated in water were measured for various concentrations. The spectra show a prominent peak around 3.80 eV, while deconvolution of the UV-vis optical absorption spectra revealed six bands centered at 3.60, 3.83, 4.15, 4.99, 5.60, and 5.76 eV. Benznidazole electronic transitions were obtained after density functional theory (DFT) calculations within the polarized continuum (PCM) model for water solvation. Molecular geometry optimizations were carried out, and the measured absorption peaks were related to specific molecular orbital transitions obtained within the time dependent DFT (TD-DFT) with excellent agreement between theory and experiment.